Palmoplantar Pustulosis: A Systematic Review of Risk Factors and Therapies - Heidemeyer K; May Lee M; Cazzaniga S; Yawalkar N; Naldi L (Dove Medical Press, 2023)
Kristine Heidemeyer,1,2 Marco May Lee,3 Simone Cazzaniga,1,2 Nikhil Yawalkar,1 Luigi Naldi2,4 1Department of Dermatology, Inselspital University Hospital of Bern, Bern, Switzerland; 2Centro Studi GISED, Bergamo, Italy; 3Section of Dermatology, Department of Clinical and Experimental Medicine, University of Parma, Parma, Italy; 4Dermatology Department, S. Bortolo Hospital, Vicenza, ItalyCorrespondence: Kristine Heidemeyer, Department of Dermatology, Inselspital University Hospital of Bern, Freiburgstrasse 34, Bern, CH-3010, Switzerland, Tel +41 31 632 20 94, Email kristine.heidemeyer@insel.chAbstract: Palmoplantar pustulosis (PPP) is a chronic, relapsing, inflammatory disease that can occur alone or in association with arthritis. There is still controversy about whether it should be separated from psoriasis or classified as pustular psoriasis. Furthermore, drug-induced paradoxical PPP is a special variant of PPP that differs from classic PPP in several ways. Treatment of PPP is still challenging, and there are a number of treatment-resistant cases. This review summarizes the risk factors for the development of PPP and the currently available treatment modalities. Female sex, smokers or ex-smokers, obesity, thyroid dysfunction, and treatment with a tumor necrosis factor (TNF)-α inhibitor have been identified as risk factors for the disease's development, severity, and course. Topical treatments and phototherapy are effective for some patients and are used as a first-line or adjuvant treatment modality. Conventional treatments including retinoids and fumaric acid show good effects and can increase the efficacy of treatment with psoralen + ultraviolet light therapy (PUVA). Ciclosporin is fast acting, but relapse mostly occurs immediately after cessation. TNF-α inhibitors are efficient, and an even better response can be achieved with IL-17 and IL-23 blockers as well as apremilast. The effect of Janus kinase inhibitors seems to be promising according to case reports, but further investigations with larger cohorts are needed.Keywords: palmoplantar, pustulosis, psoriasis, treatment, risk factors